An internet-based real-time remote automatic control laboratory for control education - ERDAL, HASAN; SAVAŞ, KENAN (ELSEVIER SCIENCE BV, 2010)
This paper describes a web based remote automatic control lab, RACL, system. This is a system that enables students do real time control experiments from a remote location (e.g. their homes) using internet and an ordinary web browser. By using this system one can select an experiment, launches that experiment, and examines real time experiment outputs by looking at charts. This system brings hope for reducing costs and improving control education quality. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Automatic control; control education; remote laboratory; distance education